Impact of working conditions and interpersonal relationships on performance of non-academic staff - Owunna, Royal; Abd Aziz, Mohd Faiq; Musa, Siti Nur Syuhada; Ajobi, Alice Omoefe (Human Resources Management Academic Research Society (HRMARS), 2023)
This study examines the impact of working conditions and interpersonal relationships on the performance of non-academic staff. Quantitative investigation employed the simple random sampling technique, this criterion suits the present study, the participants selected for sampling were heterogeneous, and simple random sampling guaranteed equal chance for the respondents, with a sample size of 220 participants for the examination. Data was collected through a self-administered questionnaire that was distributed indiscriminately and was analyzed using the statistical tool (SPSS 25.0). Pearson Chi-square test of independence and Multiple Regression was used to analyze the data. The findings of the descriptive analysis outcomes showed that the level of employee performance and working conditions was high. All the same, the level of interpersonal relationships was average. The study suggested amongst others, that to minimize the limitation of self-reporting data, further investigation is required to adopt a qualitative investigation method, future investigation should consider private institutions as respondents.